2007
DOI: 10.1518/155534307x264861
|View full text |Cite
|
Sign up to set email alerts
|

Shooting Decisions by Police Firearms Officers

Abstract: This study is an investigation into whether briefing information, which was heard prior to seeing a firearms incident in a firearms training simulator, affected British police officers' decisions to shoot, as measured by their shooting behavior. Police authorized firearms officers (AFOs) heard either threat or neutral briefing information and then saw a "shoot" (suspect shot at AFO) or "no-shoot" (suspect surrendered without shooting) scenario. AFOs were tested in one of four conditions: threat briefing with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
0
19
0
4
Order By: Relevance
“…Second, general information given to participants before they entered the room may have primed them to expect a certain amount of threat. Although previous research has suggested that briefings before experiments do not significantly affect officers’ behaviour (e.g., Mitchell & Flin, ), expectations may have played a role in the reasonably high levels of state anxiety in the LT scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Second, general information given to participants before they entered the room may have primed them to expect a certain amount of threat. Although previous research has suggested that briefings before experiments do not significantly affect officers’ behaviour (e.g., Mitchell & Flin, ), expectations may have played a role in the reasonably high levels of state anxiety in the LT scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggested that, irrespective of threatening circumstances, limited working memory capacity can increase the risk of aggressive shooting behaviour. Furthermore, Mitchell and Flin (2007) investigated whether briefing information, provided prior to seeing a firearms incident in a simulator, affected police officer's decisions to shoot in Scotland. The findings in this study suggested that briefing information did not influence the shooting decisions by the firearms officers, but they attended to the cues in the scenario and responded accordingly.…”
Section: Previous Researchmentioning
confidence: 99%
“…During the period 2002-2014, on average, there were 62 cases per year in which police threatened to make use of firearms but did not discharge their weapons (Politiet.no, 2019b). Because police use firearms so infrequently, it is difficult to determine when an officer can be regarded as experienced in this matter (Mitchell & Flin, 2007). Given these numbers, it is reasonable to argue that Norwegian police officers' recognition of armed assignments is likely to be based on situations involving no confrontation or deescalation.…”
Section: Recognitionmentioning
confidence: 99%
“…Individual preference for each style varies from high to low, and decision-making can be based on many styles; however, for each person, one style tends to dominate. Two types dominating in the police, most in line with the attitude of the officer: rational and intuitive, have been subjected to research related to the comparison of the type and time of making a decision to use the weapon and consequences of its use (Mitchell, Flin 2007;Brown, Daus 2015).…”
Section: Policemen' Individual Predispositions (Mental and Physical)mentioning
confidence: 99%